Analysis of the LPG bottling process: focus on continuous improvement - Rosa, Jorge Luiz; Feriotti, Marco Aurélio; Formigoni, Alexandre; Pohlmann , Mayara; Ribeiro , Rosinei Batista (Brazilian Journal of Production Engineering, 2022)
Currently, the industry has a constant need to efficiently use the resources it has. In this way, no proposal for improvement should be ignored, but rather studied, in order to the extract the maximum benefit, from the gain in efficiency itself regarding knowledge for future developments. Seeking to improve the existing processes at the Ultragaz company’s plant, in São José dos Campos-SP, a study was developed with the aim of optimizing the processes developed at the same plant. From the mapping of processes, identify the processes that can be improved and from there, prepare, implement and monitor the proposed changes, thus identifying inefficiencies to be minimized. During 2017, two processes were identified to be improved: the Treatment of Effluents and the Displacement and Transport of Containers belonging to other brands. In both cases, inefficiencies and opportunities for improvement were identified.